Biodiversity monitoring as a baseline for PROPER biodiversity protection program of PT. Geo Dipa Energi Dieng, Central Java, Indonesia - Hadisusanto, Suwarno (Society for Indonesian Biodiversity, 2022)
Anthropogenic activities drove an unprecedented rate of land-use change in the last century. Corporate is one of the most highlighted sectors due to the extent of the impact on the environment. Therefore, PROPER (Corporate Performance Rating Assessment for Environmental Program) was developed by the Ministry of Environment and Forestry as a safeguard to halt biodiversity loss due to corporate-related development in Indonesia. The present study analyzed the flora and fauna composition, structure, and trend in PT. Geo Dipa Energi Dieng well pad surrounding area from 2019-2021, as a critical part of the PROPER assessments. The study revealed that the study area was homogeneously dominated by shrubs-herbaceous plants, contributing to 60% of total species richness and abundance. Two dominant species were the introduced wild species Ageratina riparia and the cultivated plant Solanum tuberosum. Moreover, despite tree individual scarcity, the tree growth form was primarily constituted by introduced species with a mean abundance of 347 individuals, or 5-fold higher than native species. Acacia decurrens and Cupressus sempervirens, the introduced tree species planted during the rehabilitation program, dominated the area. The homogeneous floristic composition led to a homogenization of the fauna community, particularly birds, dominated by cosmopolitan insectivorous species. NMDS analysis and Shannon-Diversity Index also revealed that the pattern and trend among sites and years were similar, and there was an insignificant change, showing the urgency of the long-term revegetation programs to rehabilitate the ecosystem. Moreover, the presence of protected species in the study area showed that ecosystem rehabilitation is critical.